2015
DOI: 10.1016/j.econedurev.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Do completed college majors respond to changes in wages?

Abstract: In an analysis connecting labor market earnings to college major choices, we find statistically significant relationships between changes in wages by occupation and subsequent changes in college majors completed in related fields of college study between 1982 and 2012. College majors (defined at a detailed level) are most strongly related to wages observed three years earlier, when students were college freshmen. The responses to wages vary depending on the extent to which there is a strong mapping of majors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
51
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 37 publications
4
51
1
1
Order By: Relevance
“…We suggest that the likely channel 4 through which lower black STEM degree completion operates is negative expectations about future employment prospects in STEM fields as a result of increased inflows of skilled foreign-born workers. This result is consistent with research studying how students form expectations about employment outcomes for various majors and choose their own majors (Zafar, 2011;Clark, 2015;Long, Goldhaber, and Huntington-Klein, 2015;Wiswall and Zafar, 2015). Additionally, we argue that white STEM graduates were also adversely affected by the policy by being less able to find work in related occupations (or at all), which reduces earnings (Kinsler and Pavan, 2015).…”
Section: Introductionsupporting
confidence: 89%
“…We suggest that the likely channel 4 through which lower black STEM degree completion operates is negative expectations about future employment prospects in STEM fields as a result of increased inflows of skilled foreign-born workers. This result is consistent with research studying how students form expectations about employment outcomes for various majors and choose their own majors (Zafar, 2011;Clark, 2015;Long, Goldhaber, and Huntington-Klein, 2015;Wiswall and Zafar, 2015). Additionally, we argue that white STEM graduates were also adversely affected by the policy by being less able to find work in related occupations (or at all), which reduces earnings (Kinsler and Pavan, 2015).…”
Section: Introductionsupporting
confidence: 89%
“…By doing so, we add to a growing set of papers using subjective expectations data to distinguish between the role played by monetary returns versus nonpecuniary preferences in individual decisions. While several papers have recently addressed this question in the related context of college major and university choices (see, e.g., Zafar, 2011Zafar, , 2013Arcidiacono et al, 2012;Delavande and Zafar, 2014;Long et al, 2014;Stinebrickner andStinebrickner, 2014 andZafar, 2014), our paper is, to the best of our knowledge, the first to do so in the context of occupational choices.…”
mentioning
confidence: 91%
“…These occupation-specific elasticities range from 0.70 (for Business) to 0.86 (for Education), resulting in a mean elasticity across all occupations equal to 0.79. It is worth noting that these elasticities are sizable, especially in comparison with the very low earnings elasticities which have been found in the literature on college major choices (see, e.g., Beffy et al, 2012, Long et al, 2014, and Wiswall and Zafar, 2014. This further stresses the importance of considering the choice of college major and the choice of occupation as two separate, albeit related, decisions.…”
mentioning
confidence: 92%
“…Research has shown that the choice of college major is responsive to the relative pay of graduates with those majors, as in Arcidiacono (2004), or Montmarquette, Canning and Majseredjian (2002), or the relative pay of occupations related to those majors, as in Long, Goldhaber and Huntington-Klein (2014). Similarly, Freeman and Hirsch (2008) show that the number of students that graduate with a particular college major is responsive to the knowledge content of occupations and the market payoff to that knowledge content.…”
Section: Introductionmentioning
confidence: 99%